Communicating the knowledge of Youths in Owerri on the health effects of Shisha Smoking - Eustace Chinedu, Nwanekwu; Emeka Williams, Etumnu; Miriam Ifeanyi, Amaku; Williams-Etumnu, Oluchi (COMMICAST, 2025)
Recently, the prevalence of shisha smoking is alarming and it has continued to raise health concerns among smokers. The aim of this study was to find out the knowledge of youths on the health effects of smoking shisha. Hence, this study investigated the knowledge of the health effects of shisha smoking among youths in Owerri. The survey method was used for this study with a sample size of 385, which was derived from the Survey Monkey online sample size calculator. A multistage sampling technique was employed. Results showed that, at a mean of 3.2 (N = 372), there is a high prevalence of shisha smoking among youths in Owerri and its surrounding areas. The result showed that, at a mean of 3.2 (N = 372), the youths in Owerri are knowledgeable regarding the health effects of shisha smoking. It was concluded that there is a high prevalence of shisha smoking among youths in Owerri. This is even with the level of awareness and knowledge about the health effects of shisha smoking among youths in Owerri. This could be linked to the factors associated with shisha smoking. One of the contributions of the study is that it will provide the need for professionals, policymakers, and all stakeholders involved in managing the issues of smoking to see why it is essential to engage in serious campaigns so as to raise the awareness of people towards the danger or health effect of shisha smoking in society.